Dissection of phospholipases A2 reveals multifaceted peptides targeting cancer cells, Leishmania and bacteria - Peña Carrillo, María Sol (2021)
Cationic peptides bio-inspired by natural toxins have been recognized as an efficient strategy for the treatment of different health problems. Due to the specific interaction with substrates from biological membranes, snake venom phospholipases (PLA2s) represent valuable scaffolds for the research and development of short peptides targeting parasites, bacteria, and cancer cells. Considering this, we evaluated the in vitro therapeutic potential of three biomimetic peptides (pCergo, pBmTxJ and pBmje) based on three different amino acid sequences from Asp49 PLA2s. First, short amino acid sequences (12–17 in length) derived from these membranolytic toxins were selected using a combination of bioinformatics tools, including AntiCP, AMPA, PepDraw, ToxinPred, and HemoPI. The peptide, from each polypeptide sequence, with the greatest average antimicrobial index, no toxicity, and no hemolysis predicted was synthesized, purified, and characterized. According to in vitro assays performed, pBmje showed moderate cytotoxicity specifically against MCF–7 (breast cancer cells) with an EC50 of 464.85 µM, whereas pBmTxJ showed an antimicrobial effect against Staphylococcus aureus (ATCC 25923) with an MIC of 37.5 µM, and pCergo against E. coli (ATCC 25922) with an MIC of 75 µM. In addition, pCergo showed antileishmanial activity with an EC50 of 93.69 µM and 110.40 µM against promastigotes of Leishmania braziliensis and L. amazonensis, respectively. Altogether, these results confirmed the versatility of PLA2-derived synthetic peptides, highlighting the relevance of the use of these membrane-interacting toxins as specific archetypes for drug design focused on public health problems.